IMPROVING STUDENT COURSES THROUGH JAVANESE SATURDAY HABITU IN SD NEGERI RESAPOMBO 06 - Darmawan Hadi; Isna Nurul Inayati (EBTIDA': Jurnal Pendidikan Dasar Islam, 2022)
The results of observations at SD Negeri Resapombo 06 show that there has been a decline in student character which is reflected in the attitudes and speech of students who tend to be rude and impolite at school, both when interacting with peers and when interacting with teachers. To address this, the researchers plan to carry out school action research with the theme of increasing student manners through the habit of Javanese Saturdays. This type of research is school action research. This research was conducted at SD Negeri Resapombo 06 in November 2021 with the research subjects being all students at SD Negeri Resapombo. The technique of collecting data from this school action research is through qualitative data obtained from observation/ observations, interviews and document studies. This procedure includes the following stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. Based on the results of reflection, monitoring and evaluation that have been carried out, it can be concluded that cycle 1 and cycle 2 activities have increased so that all objectives of this school action research activity are declared successful.